Periodic Fever, Aphthous Stomatitis, Pharyngitis, and Cervical Adenitis Syndrome (PFAPA): A Clinical Challenge for Primary Care Physicians and Rheumatologists - Costagliola, Giorgio; Maiorino, Giuseppe; Consolini, Rita (Frontiers in Pediatrics, 2019)
Objective: To show the different physician’s approaches and the difficulties in the diagnosis and management of the Periodic Fever, Aphthous Stomatitis, Pharyngitis, and Cervical Adenitis (PFAPA) syndrome, and to quantify the impact of the disease on the families and on the healthcare system. Study design: Retrospective analysis on 40 patients diagnosed with PFAPA, focusing on the clinical phenotype, the process of diagnosis, and the management of the febrile episodes. The direct and indirect annual economic cost related to PFAPA in the period preceding the diagnosis were also investigated. Results: The median age of patients at disease onset was 1,75 years and the median time to diagnosis was 14,5 months. During the diagnostic process, only 45% of our patients was firstly addressed to rheumatologic consultation, 32,5% to otorinolaryngologist (ORL) and 22,5% to immunologic consultation. Genetic investigations were performed in the 20% of the cohort. Overall population experienced a median of 60 annual days of fever and, during the critical phase, 40% of patients received more than 5 cycles of antibiotic/year. 75% required laboratory investigations, 18 (45%) needed to access to emergency department and 15 (37,5%) have been hospitalized. The annual mean direct cost was 1659,5 € for each patient, and the estimated mean indirect cost was 5811,6 € for each parent. Conclusion: Despite a benign clinical course, PFAPA syndrome is associated with a significant impact on the patients, their families and the national healthcare system. PFAPA patients require a large number of medical examinations and laboratory or instrumental investigations during the diagnostic approach and often receive inappropriate treatments. Therefore, we suggest the necessity of a greater awareness and knowledge of the disease among primary care physicians and, finally, of the adoption of more specific diagnostic criteria.